The Effectivity of Medicinal Plant Based on Local Wisdom of Dayak Community Textbook Development on Improving Student Learning Outcome - Fathul zannah; Ayatusaadah (Jurnal Penelitian Pendidikan IPA, 2023)
Exploration of local plant germplasm as a source of biopharmaceuticals is a practice that has often been carried out by the Dayak community in Central Kalimantan, one of them is Diplazium esculentum which is believed to treat acne. Scientific testing of the effectiveness of Diplazium esculentum as an acne medication can be a source of learning in lecture activities as a medicinal plant based on local wisdom of Dayak community textbook development. This research aims to generate a local wisdom and laboratory experiment textbooks that are valid, practical and effective in Biotechnology courses, specifically on pharmaceutical biotechnology topic of biology education program, Islamic State University of Palangka Raya. This textbook development followed the model ADDIE. The results of this research showed that the textbooks that developed using ADDIE model are a) categorized very valid based on the results of an content expert (91,68%), media expert (83,58%) and practitioners' assessment (91.22%), b) practically based on limited testing of college student of biology education program in Islamic State University of Palangka Raya and c) effective based on the result of cognitive test on health biotechnology topics that had a significant effect with p-value 0.009 <Î± (Î± = 0,05). This research concluded that the textbooks based on local wisdom and laboratory experiment which were developed have been proved valid, practical, and effective to increase learning outÂcome.